TO DISCONTINUE OR TO WAIT?: INDICATIONS FOR DISCONTINUATION OF ANTI-TUBERCULOSIS DRUGS DUE TO ADVERSE EVENTS - D. A. Ivаnovа (Tuberkulez i Bolezni Lëgkih, 2018)
The objective of the study: to define indications for discontinuation of a drug causing adverse reactions during chemotherapy in tuberculosis patients. The frequency, severity, and outcomes of adverse reactions with anti-tuberculosis drugs discontinued and not were analyzed in 435 new tuberculosis patients. The severity of AE was assessed using modified criteria of NCI CTCAE version 4.0 and DMID. In 69.2% of patients (95% CI 64.7-73.3%) AE resulted in the discontinuation of at least one drug and it was associated with the significant increase of the intensive phase duration. Severe AE (severity grades 3-4) were observed in 54.3% of patients (95% CI 49.6-58.9%). In 17.0% of cases, the discontinuation of drugs could have been avoided, in 20.9% the drug had to be discontinued due to the risk of complications and irreversible damage of organs as per the signs of grade 2 of severity. The continued in-take of anti-tuberculosis drugs in case of AE of severity grade 3-4 was associated with negative changes in 20 out of 62 cases (32.2%). Indications for discontinuation of anti-tuberculosis drugs in the intensive phase of treatment include grades 3-4 of severity, the risk of irreversible damage of an organ and life-threatening conditions. Discontinuation of the drug can be discussed in case of some moderate adverse events should all available conservative measures fail.